Application of nano-porous material in ozone storage

By using nanoporous molecular sieve materials with specific pore sizes to improve the solubility of ozone in water, the problems of insufficient ozone storage and solubility are solved, and a highly efficient catalytic oxidation effect is achieved.

CN119490265AActive Publication Date: 2025-02-21SUN YAT SEN UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411560778.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-21
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

In existing technologies, ozone has low solubility and is unstable in water, making it difficult to store and limiting its application in catalytic oxidation reactions.

Method used

By employing nanoporous molecular sieve materials with a specific average pore size of 2.5–4 nm, the storage and solubility of ozone are improved through their ordered mesoporous channels.

Benefits of technology

It significantly improves the saturated solubility of ozone in water. The nanoporous material can store up to 1.95 × 10² mg of ozone per gram of water, thus enhancing the catalytic oxidation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490265A_ABST
    Figure CN119490265A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ozone storage, and particularly relates to application of a nano-porous material in ozone storage or improvement of water ozone saturation solubility, the nano-porous material is a molecular sieve, and the average pore size of the molecular sieve is 2.5-4 nm. The inventor finds that the nano-porous material with the specific average pore size has an excellent storage effect on ozone, the defect that ozone is prone to oxidative decomposition can be effectively relieved, meanwhile, the nano-porous material can remarkably improve the ozone saturation solubility of a water body, and the catalytic ozonation efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ozone storage, and more specifically, relates to the application of nanoporous materials in ozone storage. Background Art

[0002] Deep water treatment is an inevitable requirement for realizing the recycling of water resources, and it is of great significance to building a low-carbon society and promoting the construction of ecological civilization. Advanced oxidation technology (AOPs) is currently one of the most effective means to degrade toxic and harmful new pollutants. They include catalytic ozone oxidation, Fenton oxidation, electrocatalytic oxidation, photocatalytic oxidation, catalytic persulfate oxidation, etc. Among them, ozone catalytic oxidation has attracted widespread attention due to its advantages such as few by-products and simple operation, and has been applied in sewage and wastewater treatment projects.

[0003] Ozone catalytic oxidation technology can effectively degrade refractory organic pollutants through the synergistic effect of ozone oxidation and catalysts. As a new water treatment technology, catalytic ozone oxidation technology is widely used in water treatment. Generally speaking, ozone reacts with organic matter mainly through direct reaction and indirect reaction. Direct reaction is the direct reaction between ozone molecules and organic matter; indirect reaction is the reaction between ozone and water to produce strong oxidizing free radicals, which then react with organic matter. The ozone concentration in the reaction system is the key factor determining the rate of ozone catalytic oxidation reaction. Higher ozone concentration usually improves the effect of catalytic oxidation. However, the solubility of ozone in water is small, and the ozone structure is unstable and can be easily reduced to oxygen at room temperature, making it difficult to store. As a result, it is difficult to expand the application of ozone and give full play to its catalytic activity. Therefore, it is urgent to find an efficient ozone storage method or a method to increase the saturated solubility of ozone in water. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide an application of nanoporous materials in ozone storage or in improving the saturated solubility of ozone in water.

[0005] Another object of the present invention is to provide a method for increasing the saturated solubility of ozone in water.

[0006] Another object of the present invention is to provide application of the method in catalytic ozone oxidation.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] The present invention provides application of nanoporous material in ozone storage or in improving ozone saturation solubility in water. The nanoporous material is a molecular sieve; the average pore size of the molecular sieve is 2.5-4 nm.

[0009] The porous nanomaterial of the present invention is a molecular sieve having ordered mesoporous channels. The present invention has found through research that the molecular sieve having a specific average pore size and ordered mesoporous channels has an excellent storage effect on ozone, and based on its specific average pore size and nanopore structure, the saturated solubility of ozone in water can be greatly improved.

[0010] Specifically, when the average pore size of the molecular sieve is 2.5 to 4 nm, it has a good storage effect on ozone and can significantly increase the solubility of ozone in water. After adding the molecular sieve of the present invention, the saturated ozone solubility in the pores of the molecular sieve is at least 1.95×10 2 mg / g, that is, each gram of water in the pores of the nanoporous material can store 1.95×10 2 mg ozone. When the molecular sieve dosage is 1g / L, the ozone solubility of the entire suspension system is at least 0.34mg / g, which is 61.90% higher than the ozone solubility in water without molecular sieve. The inventors found in a large number of experimental studies that when the average pore size of the molecular sieve is further reduced to the micropore range, ozone is difficult to enter the molecular sieve pores, the molecular sieve's ability to accommodate ozone becomes worse, and the solubility of ozone in water decreases; when the average pore size of the molecular sieve is further increased, the molecular sieve's ability to accommodate ozone becomes worse, and the ozone solubility in water does not increase significantly.

[0011] Preferably, the average pore size of the molecular sieve is 3 to 3.8 nm. Specifically, the average pore size of the molecular sieve in the present invention can be 3 nm, 3.1 nm, 3.2 nm, 3.3 nm, 3.4 nm, 3.5 nm, 3.6 nm, 3.7 nm, 3.8 nm, etc., or an interval range formed by any of the above values, such as 3.1 to 3.5 nm, 3.2 to 3.6 nm, etc., and the present invention is not limited thereto.

[0012] Preferably, the specific surface area of ​​the nanoporous material is 800 to 1450 m 2 More specifically, the specific surface area of ​​the nanoporous material is 1084 to 1402 m 2 / g. Specifically, the specific surface area of ​​the nanoporous material in the present invention can be 1084.8nm, 1130nm, 1180nm, 1230nm, 1280nm, 1330nm, 1380nm, 1401.9nm, etc., or an interval range formed by any of the above values, such as 1084.8-1401.9nm, 1130-1380nm, etc., but the present invention is not limited thereto.

[0013] Preferably, the pore volume of the nanoporous material is 0.7 to 1.5 cc / g.

[0014] Preferably, the molecular sieve may be a silicon-based molecular sieve, or a metal-doped modified silicon-based molecular sieve.

[0015] Preferably, the silicon-based molecular sieve is MCM-41 molecular sieve, or other silicon-based molecular sieves that can be prepared to have an average pore size of 2.5 to 4 nm.

[0016] The silicon-based molecular sieve or metal-doped modified silicon-based molecular sieve of the present invention may be commercially available or may be synthesized in a laboratory according to conventional methods.

[0017] The present invention provides the silicon-based molecular sieve preparation method as a reference, and the specific preparation method is: mixing a silicon source, a surfactant and a pore-enlarging agent, adjusting the pH to 10-12, crystallizing at 20-35°C, taking the crystals and removing the surfactant to obtain the obtained silicon-based molecular sieve.

[0018] Preferably, the molar ratio of the silicon source, the surfactant and the pore expanding agent is 10:1:1-3.

[0019] The present invention provides a preparation method of the metal-doped modified silicon-based molecular sieve as a reference. The specific preparation method is: mixing a silicon source, a metal salt, a surfactant, and a pore-enlarging agent, adjusting the pH to 10-12, crystallizing at 20-35°C, taking the crystals and removing the surfactant to obtain the molecular sieve.

[0020] Preferably, the molar ratio of silicon to metal atoms is 25 to 200: 1. Further preferably, the molar ratio of silicon to metal atoms is 25 to 100: 1. The inventors have found that when the molar ratio of silicon to metal is 25 to 100: 1, the prepared metal-doped modified silicon-based molecular sieve has a better storage effect on ozone, and the saturated solubility of ozone in water is higher.

[0021] Preferably, the metal in the metal salt is aluminum or tin.

[0022] Preferably, the molar ratio of the silicon source, the surfactant and the pore expanding agent is 10:1:1.8-2.

[0023] Preferably, the silicon source is a silicon source conventionally used in the preparation of silicon-based molecular sieves in the art; more specifically, the silicon source includes but is not limited to tetraethyl silicate and the like.

[0024] Preferably, the surfactant is a conventional surfactant conventionally used in the preparation of silicon-based molecular sieves in the art; more specifically, the surfactant includes but is not limited to hexadecyltrimethylammonium bromide and the like.

[0025] Preferably, the pore expanding agent is a conventional pore expanding agent conventionally used in the preparation of silicon-based molecular sieves in the art; more specifically, the pore expanding agent includes but is not limited to 1,3,5-trimethylbenzene and the like.

[0026] Preferably, the crystallization time is 2 to 3 days.

[0027] The present invention also provides a method for improving the saturated solubility of ozone in water, which includes introducing ozone into a water environment dispersed with nanoporous materials; the nanoporous materials are molecular sieves; and the average pore size of the molecular sieves is 2.5-4 nm.

[0028] Preferably, when the concentration of the nanoporous material in the water environment is 1 to 1.5 g / L, the intake concentration of ozone is 1 to 2.5 mg / L. Within this range of intake ozone concentration, the saturated solubility of ozone is higher, and further increasing the intake concentration of ozone does not increase the saturated solubility of ozone much.

[0029] Preferably, the pH of the water environment is 3 to 10. Preferably, the pH of the water environment is 3 to 7. Within this pH range, the saturated solubility of ozone is higher.

[0030] Preferably, the temperature of the water environment is 0-40° C. Within this temperature range, the saturated solubility of ozone is higher.

[0031] Additionally, the present invention also protects the use of the method in catalytic ozone oxidation.

[0032] The present invention has the following beneficial effects:

[0033] The present invention provides an application of a nanoporous material in ozone storage or in improving the saturated solubility of ozone in water. The nanoporous material is a molecular sieve, and the average pore size of the molecular sieve is 2.5 to 4 nm. The inventors have found that the nanoporous material with the specific mesopore size of the present invention has an excellent storage effect on ozone, which can effectively alleviate the disadvantage of easy oxidation and decomposition of ozone. By using the specific nanoporous material of the present invention, each gram of water in the pores of the nanoporous material can store at least 1.95×10 2 mg ozone, this nanoporous material with high active ozone content is very beneficial to improve the efficiency of ozone catalytic oxidation. At the same time, the nanoporous material of the present invention can significantly improve the saturated solubility of ozone in water. When the molecular sieve dosage is 1g / L, the ozone solubility of the entire suspension system is at least 0.34mg / g and can reach up to 0.67mg / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a diagram of the ozone dissolution device. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0036] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0037] Examples 1 to 3 Aluminum-doped MCM-41 molecular sieve with an average pore size of about 3.2 nm

[0038] Tetraethyl silicate and aluminum sulfate were mixed at a silicon:aluminum molar ratio of 200, 100 or 50, and added to a uniform mixture of a surfactant (hexadecyltrimethylammonium bromide, CTAB) and a pore-enlarging agent (1,3,5-trimethylbenzene) (when the silicon:aluminum molar ratio was 200, the molar ratio of the surfactant to the pore-enlarging agent was 1:2; when the silicon:aluminum molar ratio was 100, the molar ratio of the surfactant to the pore-enlarging agent was 1:1.9; when the silicon:aluminum molar ratio was 50, the molar ratio of the surfactant to the pore-enlarging agent was 1:1.9). The molar ratio of surfactant to pore enlarging agent is 1:1.8), the pH is adjusted to 11 with ammonia water, crystallized at room temperature for 3 days, and the crystals are calcined at 550°C for 6 hours to remove the surfactant to obtain MCM-41 molecular sieves containing different silicon-aluminum ratios. The obtained MCM-41 is expressed as Al-M41(x), where x represents different Si / Al ratios. The final molecular sieves are recorded as Al-M41(200), Al-M41(100) and Al-M41(50).

[0039] Examples 4 to 6: MCM-41 molecular sieves with average pore sizes of approximately 2.6 nm, 3.2 nm, and 3.6 nm

[0040] 5 mL of tetraethyl silicate was added to a mixture of 120 mL of CTAB and 1,3,5-trimethylbenzene (TMB), the pH was adjusted to 11 with aqueous ammonia, and then crystallized at room temperature for 3 days and calcined at 550°C for 6 hours to remove the surfactant, thereby obtaining MCM-41 molecular sieves with different pore sizes.

[0041] Wherein, when the molar ratio of CTAB to 1,3,5-trimethylbenzene in the mixture is 1:1, the average pore size of the prepared MCM-41 molecular sieve is 2.6 nm, recorded as M41-2.6;

[0042] When the molar ratio of CTAB to 1,3,5-trimethylbenzene in the mixture is 1:2, the average pore size of the prepared MCM-41 molecular sieve is 3.2 nm, recorded as M41-3.2;

[0043] When the molar ratio of CTAB to 1,3,5-trimethylbenzene in the mixture is 1:3, the average pore diameter of the prepared MCM-41 molecular sieve is 3.6 nm, which is recorded as M41-3.6.

[0044] Comparative Example 1: MCM-41 molecular sieve with an average pore size of about 5.9 nm

[0045] CTAB: ammonia: water: TMB: tetraethyl silicate were mixed in a molar ratio of 0.1:15:66.7:1:1, and then hydrothermally heated at 110°C for 48 hours. The precipitate was washed and dried, and then calcined at 550°C for 6 hours to obtain MCM-41 molecular sieve with an average pore size of 5.9 nm, recorded as M41-5.9.

[0046] Comparative Example 2: MCM-41 molecular sieve with an average pore size of about 11.8 nm

[0047] Water: CTAB: sodium hydroxide: TMB: fumed silica were mixed in a molar ratio of 20:0.1:0.25:1.3:1, and a hydrothermal reaction was carried out at 70°C for 5 hours. The precipitate was washed, then dried at 115°C, and then calcined at 550°C for 8 hours to obtain an MCM-41 molecular sieve with an average pore size of 11.8 nm, named M41-11.8.

[0048] Material characterization

[0049] The basic physical properties of Examples 1 to 6, Comparative Examples 1 and 2, and commercially available SBA-15 molecular sieve, zeolite molecular sieve, and 4A molecular sieve are shown in Table 1.

[0050] Table 1

[0051] Nanoporous Materials <![CDATA[Specific surface area m 2 / g]]> Mesopore volume cc / g Average pore size of mesopores (nm) Al-M41(200) 1084.8 1.1 3.2 Al-M41(100) 1137.5 1.1 3.2 Al-M41(50) 1106.1 1.0 3.2 M41-2.6 808.0 0.7 2.6 M41-3.2 1401.9 1.0 3.2 M41-3.6 1195.4 1.5 3.6 M41-5.9 955.2 1.4 5.9 M41-11.8 495.5 1.4 11.8 SBA-15 molecular sieve 845.4 0.9 7.7 Zeolite molecular sieve 365.5 0.2 2.2 4A molecular sieve 484.5 0.2 0.4

[0052] Application Example 1

[0053] Experimental materials (nanoporous materials): nanoporous materials prepared in Examples 1 to 6 and Comparative Examples 1 and 2, and commercially available SBA-15 molecular sieve, zeolite molecular sieve, and 4A molecular sieve.

[0054] Experimental method: The experimental process is as follows Figure 1 As shown, the details are as follows:

[0055] Add test water to the reaction column at one time, add nanoporous material with a concentration of 1g / L, and rotate at high speed to disperse to form a suspension or do not add any material (pure water); open the constant temperature water bath of model DF-101S or the cold trap of model DLSB-50L, and let the constant temperature water flow through the jacket of the bubbling column to maintain the test water in the reaction column at 25℃; adjust the pressure valve to maintain the pressure in the reaction column at 0.1MPa; use the ozone generator of model YE-TG-01PⅡ to generate ozone gas , high-purity oxygen is used as the oxygen source; ozonated gas (ozone inlet concentration is 1 mg / L) is dispersed into the test water from the titanium alloy aeration head at the bottom of the reaction column, and the excess ozone after saturation is removed with a potassium iodide absorption bottle. The gas flow, temperature, pressure, stirring speed, the reading of the gas-phase ozone concentration detector at the inlet, and the reading of the gas-phase ozone concentration detector at the outlet are recorded. Every 1 minute, the suspension in the reaction column is taken to detect its ozone concentration. When the ozone concentration tends to be stable, the ozone dissolution has reached saturation.

[0056] When ozone is dissolved to saturation, the ozone concentration in the suspension is detected according to the iodine titration steps of GB / T5750.11-2006 and GB 28232-2011. The concentration of sodium thiosulfate titration solution (B) is in moles per liter (mol / L); the volume of sodium thiosulfate titration solution consumed during ozone water titration (A Na ), the unit is milliliter (mL). The specific experimental steps are: place the suspension (ozone water: liquid containing ozone) and potassium iodide solution containing sulfuric acid in a closed container, place it in a high-speed centrifuge and rotate it at high speed for 5 minutes, and then quickly calibrate the supernatant with a calibrated sodium thiosulfate solution to calculate the saturated solubility of ozone in the suspension containing nanoporous materials. Further, based on the volume of pure water and the volume of water in the pores of the nanoporous material, the ozone solubility of open water and nano-confined water is calculated according to the following formulas (1) and (2), respectively. The experimental results are shown in Table 2:

[0057]

[0058] C O3 —Ozone saturated solubility, mg / g;

[0059] A Na —Amount of sodium thiosulfate standard solution used, mL;

[0060] B—concentration of sodium thiosulfate standard solution, mol / L;

[0061] m0—Ozone water sampling weight, g.

[0062]

[0063] C O3-pore—Saturated solubility of ozone in the pores, mg / g, i.e., the number of mg of ozone that can be stored per gram of water in the pores of the nanoporous material;

[0064] C1—saturated solubility of ozone in the entire suspension system, mg / g;

[0065] m1—sampling weight of suspension, g;

[0066] C2—saturated solubility of ozone in the suspension after removing the nanoporous material, mg / g;

[0067] m2—weight of the suspension after removing the nanoporous material, g;

[0068] m—The weight of water in the pores of the material contained in the suspension, g.

[0069] Table 2 Ozone concentration detected in each embodiment and comparative example

[0070] Group Nanoporous Materials <![CDATA[C O3-pore / mg / g]]> <![CDATA[C1 / mg / g]]> <![CDATA[C2 / mg / g]]> 1 Al-M41(200) <![CDATA[2.29×10 2 ]]> 0.47 0.21 2 Al-M41(100) <![CDATA[3.39×10 2 ]]> 0.58 0.21 3 Al-M41(50) <![CDATA[4.77×10 2 ]]> 0.67 0.21 4 M41-2.6 <![CDATA[1.39×10 2 ]]> 0.34 0.21 5 M41-3.2 <![CDATA[1.98×10 2 ]]> 0.41 0.21 6 M41-3.6 <![CDATA[1.95×10 2 ]]> 0.40 0.21 7 M41-5.9 <![CDATA[0.60×10 2 ]]> 0.30 0.21 8 M41-11.8 <![CDATA[0.41×10 2 ]]> 0.27 0.21 9 SBA-15 <![CDATA[0.53×10 2 ]]> 0.29 0.21 10 Zeolite molecular sieve <![CDATA[0.20×10 2 ]]> 0.23 0.21 11 4A molecular sieve 0 0.21 0.21 12 none / 0.21 /

[0071] Experimental results:

[0072] It can be seen from Group 12 in Table 2 that under the conditions of a pressure of 0.1 MPa and an ozone inlet concentration of 1 mg / L (the concentration of ozone in the gas phase), the saturated solubility of ozone in pure water without adding any material is 0.21 mg / g, that is, each gram of water contains 0.21 mg of ozone.

[0073] Adding Al-doped modified MCM-41 molecular sieves Al-M41(200), Al-M41(100) or Al-M41(50) to water can significantly increase the saturated solubility of ozone in water, compared with group 12 in Table 2. The saturated solubility of ozone in the entire water suspension (C1) is increased to 0.47, 0.58 and 0.67 mg / g, respectively. As the silicon-aluminum ratio decreases (the higher the Al content, the more acid sites), the saturated ozone solubility also gradually increases. Moreover, according to the calculation of the saturated solubility of ozone in the pores (C1) of Al-M41(200), Al-M41(100) and Al-M41(50), the saturated solubility of ozone in the pores (C1) is 0.47, 0.58 and 0.67 mg / g, respectively. O3-pore ) are 2.29×10 2 ,3.39×10 2 and 4.77×10 2 mg / g, that is, introducing ozone into a water body in which the nanoporous material of the present invention is dispersed can not only significantly increase the saturated solubility of ozone in the entire water body, but also the nanoporous material of the present invention can achieve a better effect of accommodating ozone.

[0074] After adding 1g / L of M41-11.8, M41-5.9, M41-3.6, M41-3.2 and M41-2.6 to the water, the ozone saturation solubility (C1) of the entire suspension system increased to 0.27, 0.30, 0.40, 0.41 and 0.34 mg / g respectively. According to calculations, the saturated solubility of ozone in the pores (C O3-pore ) are 0.41×10 2 , 0.60×10 2 , 1.95×10 2 , 1.98×10 2 and 1.39×10 2 The above data differences indicate that the saturated solubility of ozone increases first and then decreases with the increase of the average pore size of the nanoporous material. When the average pore size of the nanoporous material is between 2.6nm and 3.6nm, the saturated solubility of ozone in the entire suspension system increases by 61.90% to 95.24% compared with that without adding nanoporous material.

[0075] From the experimental results in Table 2, we can see that the storage effect of SBA-15 molecular sieve (with a larger average pore size of 7.7 nm) is not as good as that of 3 nm MCM-41, and the solubility in the pores is only about 0.53×10 2 mg / g, the ozone solubility in the entire suspension system is 0.29 mg / g; the effect of zeolite molecular sieve is also poor, about 0.20×10 2 mg / g, the ozone solubility in the entire suspension system is 0.23 mg / g, because it has a small pore size (micropores) and can easily catalyze the decomposition of ozone; 4A molecular sieve has an average pore size of 4 angstroms, ozone molecules can hardly enter, and it has almost no storage effect on ozone, and the ozone solubility in the entire suspension system is 0.21 mg / g.

[0076] The above experimental results show that dispersing molecular sieves with an average pore size of 2.5nm to 4nm in water can not only significantly increase the solubility of ozone in the system, but also achieve a good ozone accommodation effect. When the average pore size is further increased, the ozone solubility in the system and the ozone accommodation capacity of the molecular sieve are significantly reduced.

[0077] Application Example 2

[0078] Referring to the experimental method and test method of Application Example 1, the saturated ozone solubility in the M41-3.2 hole was tested under different ozone inlet concentration environments, specifically: the test was carried out under ozone inlet concentrations of 1.0, 1.5, 2.0, and 2.5 mg / L.

[0079] Experimental results: As the inlet concentration increases from 1 mg / L to 2.5 mg / L, the saturated ozone solubility in the M41-3.2 hole also increases from 1.98×10 2 mg / g increased to 2.72×10 2 mg / g, that is, increasing the ozone inlet concentration is beneficial to the improvement of the saturated solubility of ozone in the pores.

[0080] Application Example 3

[0081] Referring to the experimental method and test method of Application Example 1, the saturated ozone solubility in the M41-3.2 pores was tested under different pH environments, specifically: testing was performed under acidic (pH 3.0), neutral (pH 6.7), and alkaline (pH 10.0) conditions.

[0082] Experimental results: As the pH environment changes from alkaline to neutral and acidic, the saturated ozone solubility in the M41-3.2 pore also increases from 0.84×10 2 mg / g increased to 2.14×10 2 mg / g, which means that in an acidic environment it is beneficial to the improvement of the saturated solubility of ozone in the pores.

[0083] Application Example 4

[0084] Referring to the experimental method and test method of Application Example 1, the saturated ozone solubility in the M41-3.2 hole was tested under different temperature environments, specifically: the test was carried out at 0, 20, 40, and 60°C.

[0085] Experimental results: As the temperature drops from 60℃ to 0℃, the saturated ozone solubility in the M41-3.2 pore also increases from 0.25×10 2 mg / g increased to 4.57×10 2 mg / g, which means that it is beneficial to the improvement of the saturated solubility of ozone in the pores under low temperature environment.

[0086] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. Application of nanoporous materials in ozone storage or in improving the saturated solubility of ozone in water, characterized in that: The nanoporous material is a molecular sieve; the average pore size of the molecular sieve is 2.5-4 nm.

2. The use according to claim 1, characterized in that: The average pore size of the molecular sieve is 3 to 3.8 nm.

3. The application according to claim 1, characterized in that: The specific surface area of ​​the nanoporous material is 800 to 1450 m 2 / g.

4. The use according to claim 1, characterized in that: The pore volume of the nanoporous material is 0.7-1.5 cc / g.

5. The use according to claim 1, characterized in that: The molecular sieve is prepared by mixing a silicon source, a surfactant and a pore-enlarging agent, adjusting the pH to 10-12, crystallizing at 20-35° C., and removing the surfactant from the crystals to obtain the molecular sieve; Alternatively, a silicon source, a metal salt, a surfactant and a pore-enlarging agent are mixed, the pH is adjusted to 10-12, crystallized at 20-35° C., and the surfactant is removed from the crystals to obtain the product.

6. The use according to claim 5, characterized in that: The molar ratio of silicon to metal is 25 to 200:

1.

7. A method for increasing the saturated solubility of ozone in water, characterized in that: Passing ozone into a water environment in which the nanoporous material is dispersed; The nanoporous material is a molecular sieve; the average pore size of the molecular sieve is 2.5-4 nm.

8. The method according to claim 7, characterized in that: The temperature of the water environment is 0-40°C.

9. The method according to claim 7, characterized in that: The pH of the water environment is 3-10.

10. Use of the method according to any one of claims 7 to 9 in catalytic ozone oxidation.

Citation Information

Patent Citations

  • Method for preparing aluminium-containing MCM-41 molecular sieve

    CN101205073A

  • Porous support, preparation method and application thereof, catalyst, and hydrocracking method

    CN103028443A

  • Method for removing nitrogen-containing compound from diesel oil by adsorbing

    CN103184065A

  • Preparation method and application of Co-Mn-MCM-41 molecular sieve

    CN105435829A

  • Method for treating wastewater by ozone catalytic wet oxidation

    CN111377525A